INDEKS PENILAIAN PETANI PADA HUTAN RAKYAT DI KECAMATAN JABIREN RAYA KALIMANTAN TENGAH: Index Forest Farmer People's Judgment In District Jabiren Raya Of Central Kalimantan - Afitah, Ise (Anterior Jurnal, 2017)
This study aims to conduct quantitative assessment of farmers' performance in building community forests in terms of physical aspects of the plant (appearance) on the land in community forestry programs and assessing the socio-economic aspects of farmers (in this case the increase of farmer's resources, Acceptance of development funds for community forests and labor). This research was conducted in 2 (two) villages, namely Jabiren village and Garung village. Both villages are in Jabiren Raya District, Pulang Pisau Regency, Central Kalimantan Province. The time required in the implementation of this research is effectively carried out for 4 (four) months is from March to June 2017. The general assessment of the farmer's performance success on the physical aspects of the plant is the failing classification (the result of poor judgment). In Jabiren village there are 12 farmers categorized as failing from 20 existing farmers (60%) while in Garung village there are 10 farmers fall into the failed category of 15 existing farmers (66.7%).